Hubungan Kompensasi dan Motivasi Berprestasi Dengan Kualitas Pelayanan Publik Di Lingkungan Kecamatan Larangan Kota Tangerang - Rudy, Rudy; Suhifatullah, M. I.; Sabur, Ambuy; Mulyadi, Edi (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2021)
Service relationship is a shared responsibility. Purpose wants to know (1). Service quality compensation relationship (2). The relationship between achievement motivation and service quality (3). Compensation relationship, achievement motivation with service quality. Method: Quantitative approach describes mathematical statistics. Data collection techniques through questionnaires, surveys, study documentation. Conclusion: (a). Service quality compensation relationship ry.1 = 0.633 > rtable (rtable = 0.195 at = 0.05, rtable = 0.256 at = 0.01). (b). The relationship between achievement motivation, service quality correlation ry.2 = 0.602 > rtable (rtable = 0.195 at = 0.05 and rtable = 0.256 at = 0.01) (c). There is a correlation between achievement motivation ry.1.2 = 0.751 > rtable (rtable = 0.195 at = 0.05 and rtable = 0.256 at = 0.01). Keywords: Compensation, Motivation, Public Service